2016
DOI: 10.3732/ajb.1600176
|View full text |Cite
|
Sign up to set email alerts
|

Prior exposure to freezing stress enhances the survival and recovery of Poa pratensis exposed to severe drought

Abstract: Our results demonstrate that multiple stresses that occur over different seasons can interact; this interaction is highly relevant to herbaceous species in northern temperate regions that are experiencing more intense and frequent stress as a result of changes in snow cover and extreme climatic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…More lignified tissues were also found in grasses species with greater embolism resistance (Lens et al., ). As Kong and Henry () demonstrated that prior exposure to freezing stress enhanced Poa pratensis drought survival, some trait values are likely to benefit tolerance to both types of dehydration stresses. Our results showed that Mediterranean populations, which expressed summer dormancy, always had narrower leaves than other origins of D. glomerata , together with a high leaf dry matter content, that is traits values that have been previously mentioned as drought‐adaptive (Bartlett, Scoffoni, & Sack, ; Meng et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More lignified tissues were also found in grasses species with greater embolism resistance (Lens et al., ). As Kong and Henry () demonstrated that prior exposure to freezing stress enhanced Poa pratensis drought survival, some trait values are likely to benefit tolerance to both types of dehydration stresses. Our results showed that Mediterranean populations, which expressed summer dormancy, always had narrower leaves than other origins of D. glomerata , together with a high leaf dry matter content, that is traits values that have been previously mentioned as drought‐adaptive (Bartlett, Scoffoni, & Sack, ; Meng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, plants express variable trait values adapted to fluctuating biotic factors (Fajardo & Siefert, ; McKown, Guy, Azam, Drewes, & Quamme, ). For example, the accumulation of tiller base fructans was associated with both higher drought and higher frost survival (Kong & Henry, ; Sanada et al., ; Volaire et al., ) as it allows cells membrane stabilization (Livingston, Hincha, & Heyer, ; Vereyken, Chupin, Hoekstra, Smeekens, & De Kruijff, ). This accumulation occurs during late spring in drought‐adapted populations to improve summer drought survival, whereas Nordic populations adapted to freezing climatic conditions accumulate fructans in autumn (Østrem, Rapacz, Jørgensen, & Höglind, ; Sanada et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought tolerance in plants can be positively correlated with freezing tolerance (Cloutier and Siminovitch, ; Blödner et al., ), and drought‐freeze interactions (where prior drought exposure increases subsequent freezing tolerance) can significantly alter plant physiological responses (Hoffman et al., ) and growth (Kreyling et al., ). Likewise, freeze‐drought interactions (where prior freezing increases subsequent drought tolerance) also can impact plant physiology (Horváth et al., ; Grudkowska and Zagdanska, ; Hossain et al., ) and plant growth (Kong and Henry, ). Collectively, these responses have been described as cross acclimation or stress memory (Walter et al., ).…”
mentioning
confidence: 99%
“…When the order of the stressors is switched, and plants are exposed to drought immediately after freezing, there also are higher concentrations of antioxidants when compared to drought‐only plants (Horváth et al., ; Grudkowska and Zagdanska, ; Hossain et al., ). However, prolonged elevation of soluble sugars concentrations after drought was not responsible for increased freezing tolerance in Poa pratensis L. (Kong and Henry, ), nor did the retention of soluble sugars after freezing stress influence drought tolerance in this species (Kong and Henry, ).…”
mentioning
confidence: 99%